Peran Kiai Dalam Mensukseskan Pembelajaran Kitab Kuning (Studi Kasus KH. Abdul Haris Pengasuh Pondok Pesantren Al-Bidayah Tegalbesar Kaliwates Jember) - Wahyono, Imam (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2017)
The existence of pesantren as a religious education institution is a reality that can not be denied. Throughout history, the boarding school continues to pursue and improve its quality. Pesantren as an institution that accompanies Islamic da’wah in Indonesia has a pluralistic perception. To realize the pluralistic perception, especially the purpose of pesantren in the field of religious intellectuals, pesantren as an educational institution can make it happen through the study of the classic book commonly. In its learning activities, pesantren and the yellow book are two inseparable sides of Islamic education in Indonesia, even without the existence and teaching of the yellow book, an educational institution is not called pesantren. To keep pesantren as the center of Islamic studies, maintenance, and the yellow book remain the main characteristic. Of course, the role of Kiai through his leadership is very influential and decisive, it is clear from the fact that some boarding schools can not grow or extinct because the figure of Kiai as a leader in the boarding school can not play the role properly. Keywords: Kiai, Leadership, Islamic Studies